Managing Carbon Emission in X Supermarket at one of Mining Company in Papua: A Case Study for Better Solution - Nugroho, Andreas Teddy Ananto; Handayani, Yulia Dwi; Choirul, Muhammad; Rochman, Nur; Susilowati, Indah (Journal La Lifesci, 2026)
The economic calculation of carbon emissions from a human activity is very helpful to analyze the emissions produced from waste generation and electrical energy consumption. The waste produced in activities at supermarket X has been sorted and separated from organic and non-organic waste. The electrical energy consumed by supermarket X is also large, but in the financing it is all paid by PT Y as the supermarket's shelter. The awareness of consumers and employees of the supermarket is also high regarding cleanliness and waste disposal.